Performance of SARS-CoV-2 Antigen-Detecting Rapid Diagnostic Tests for Omicron and Other Variants of Concern - Raïch-Regué, Dàlia; Muñoz-Basagoiti, Jordana; Perez-Zsolt, Daniel; Noguera-Julian, Marc; Pradenas, Edwards; Riveira-Muñoz, Eva; Giménez, Neus; Carabaza, Assumpta; Giménez, Francesc; Saludes, Verónica; Martró, Elisa; Robert, Neus; et al. (Frontiers in Microbiology, 2022)
SARS-CoV-2 antigen-detecting rapid diagnostic tests (Ag-RDTs) are an easy-to-use diagnostic tool to identify contagious individuals and reduce new infections. Yet, to be effective, Ag-RDTs require detection of distinct variants of concern (VOC) with high analytical sensitivity. Here we found that VOC diverge at the nucleocapsid protein used by four commercial Ag-RDTs for viral detection. Relative to the original D614G variant, there was a 10-fold loss of detection for the Delta and Alpha variants in certain Ag-RDTs, a reduction above the threshold required to isolate viable virus. However, Beta and Omicron variants did not lose detection capacity. As new VOC arise, successful contact tracing will require continuous monitoring of Ag-RDTs performance.